Design of bilayer tablets using modified dioscorea starches as novel excipients for immediate and sustained release of aceclofenac soduim (2015)
Bilayer tablets of aceclofenac sodium were developed using carboxymethylated white yam (Discorearotundata) starch (CWY)for a fast release layer (2.5, 5.0, and 7.5% w/w), and acid hydrolyzed bitter yam (Dioscoreadumetorum) starch (ABY) for a sustaining layer(27% w/w). Sodium starch glycolate (SSG) and hydroxypropyl methyl cellulose (HPMC) were used as standards. The starches were characterized using Fourier Transform Infrareds pectroscopy(FT- IR), particle size, swelling power, densities and flow analyses. Mechanical properties of the tablets were evaluated using crushing strength and friability while release properties were evaluated using disintegration and dissolution times. Distinctive fingerprint differences between the native and modified starches were revealed by FT-IR. Carboxymethylation produced starches of significantly (p<0.05) higher swelling and flow properties while acid- modification produced starches of higher compressibility. Bilayer tablets containing ABY had significantly higher crushing strength and lower friability values (p<0.05) than those containing HPMC. Crushing strength increased while friability values decreased with increase in CWY. Generally tablets containing the modified Dioscorea starches gave faster (p<0.05) disintegration times and produced an initial burst release to provide the loading dose of the drug from the immediate-release layer followed by sustained release (300±7.56– 450±11.55min). The correlation coefficient (R2) and chi- square (χ2) test were employed as error analysis methods to determine the best- fitting drug release kinetic equations. Invitro dissolution kinetics generally followed the Higuchi and Hixson- Crowell models via a non-Fickian diffusion-controlled release. Carboxymethylated white yam starch anda cid- modified bitter yam starch could serve as cheaper alternative excipients in bilayer tablet formulations for immediate and sustained release of drugs respectively, particularly where high mechanical strength is required.